Estimating residential energy consumption in metropolitan areas: A microsimulation approach. (15th July 2018) - Zhang, Wenwen; Robinson, Caleb; Guhathakurta, Subhrajit; Garikapati, Venu M.; Dilkina, Bistra; Brown, Marilyn A.; Pendyala, Ram M.
Abstract: Prior research has shown that land use patterns and the spatial configurations of cities have a significant impact on residential energy demand. Given the pressing issues surrounding energy security and climate change, there is renewed interest in developing and retrofitting cities to make them more energy efficient. Yet deriving micro-scale residential energy footprints of metropolitan areas is challenging because high resolution data from energy providers is generally unavailable. In this study, a bottom-up model is proposed to estimate residential energy demand using datasets that are commonly available in the United States. The model applies novel machine learning methods to match records in the Residential Energy Consumption Survey with Public Use Microdata samples. This matching and machine learning produce a synthetic household energy distribution at a neighborhood scale. The model was tested and validated with data from the Atlanta metropolitan region to demonstrate its application and promise. Highlights: Machine learning algorithms can address energy consumption data gaps. Residential Energy Consumption Survey matched with synthesized households to generate neighborhood energy footprints. Validation uses zip code power consumption data provided by the energy provider.